2012
DOI: 10.1111/j.1467-873x.2012.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Work in Curricular Markets: Conditions of Design and Relations Between the International Baccalaureate Diploma and the Local Curriculum

Abstract: School‐level strategy enabled by neoliberal choice policies can produce internal curricular markets whereby branded curricula such as the International Baccalaureate are offered alongside the local government curriculum in the same school. This project investigated how such curricular markets operating in Australian schools impacted on teachers' work. This article reports on teachers work in three case study schools that offered both the International Baccalaureate Diploma (IBD) program and the local senior sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…Various studies have shown that schools teach students the skills and dispositions they perceive to be relevant to their students' respective 'imagined futures' (Ball, 2003;Doherty & Shield, 2012;Goren & Yemini, 2017b). Thus, teachers as critical agents within these spaces are likely to acknowledge and promote cosmopolitanism for children to whom such dispositions are deemed most relevant to their current and anticipated future social status -we see this, for instance, in studies in Israel (Goren & Yemini, 2017b) and Germany (Kotzyba et al, 2018).…”
Section: Integration Of Cosmopolitan Values Within the Local Curriculamentioning
confidence: 87%
See 2 more Smart Citations
“…Various studies have shown that schools teach students the skills and dispositions they perceive to be relevant to their students' respective 'imagined futures' (Ball, 2003;Doherty & Shield, 2012;Goren & Yemini, 2017b). Thus, teachers as critical agents within these spaces are likely to acknowledge and promote cosmopolitanism for children to whom such dispositions are deemed most relevant to their current and anticipated future social status -we see this, for instance, in studies in Israel (Goren & Yemini, 2017b) and Germany (Kotzyba et al, 2018).…”
Section: Integration Of Cosmopolitan Values Within the Local Curriculamentioning
confidence: 87%
“…The experience of visiting, working and residing in different countries can lead individuals to form new conceptions of themselves and their national and ethnic identity (Ball & Nikita, 2014;Harvey & Beaverstock, 2017;Maxwell & Aggleton, 2016). Studies of mobile professionals with families note the importance of the "imagined future" that begins to shape motivations and concerns around their mobility (Doherty & Shield, 2012;Favell, 2008). Thus, GMC parents might seek to ensure their children have access to the resources that could facilitate their continued high-status mobility in the future, in their own work lives and to guard their futures against .…”
Section: The Encroachment Of the Global Middle Classes Within Local Ementioning
confidence: 99%
See 1 more Smart Citation
“…Maxwell and Aggleton 2016). Studies of mobile professionals with families note the importance of the "imagined future" that begins to shape motivations and concerns around their mobility (Doherty and Shield 2012;Favell 2008). Thus, GMC parents might seek to ensure their children have access to the resources that could facilitate their continued high-status mobility in the future and in their own work lives and to guard their futures against increasing uncertainty.…”
Section: The Encroachment Of the Global Middle Classes Within Local Ementioning
confidence: 99%
“…Th e purpose of the developed local curriculum is to preserve and develop the uniqueness and culture of a given region, introducing culture through learning activities in an eff ective way. In addition, schools that are trusted to manage the curriculum become more confi dent (Doherty & Shield, 2012). Th e ability and capacity of teachers are better and able to innovate with the emergence of the local curriculum (Sahasewiyon, 2004).…”
Section: Samsul Hadi Dedek Andrianmentioning
confidence: 99%